2021
DOI: 10.1002/lpor.202000498
|View full text |Cite
|
Sign up to set email alerts
|

Active Stabilization of Terahertz Semiconductor Dual‐Comb Laser Sources Employing a Phase Locking Technique

Abstract: Dual-comb sources with equally spaced and low phase noise frequency lines are of great importance for high resolution spectroscopy and metrology. In the terahertz frequency range, electrically pumped semiconductor quantum cascade lasers (QCLs) are suitable candidates for frequency comb and dual-comb operation. Although free running terahertz QCLs can be operated as frequency combs and dual-comb sources, the phase noise originated from the carrier frequency and repetition rate instabilities are relatively high,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…The Allan deviation is a classic statical method that has been widely used to evaluate the stability of a signal with time. For the frequency or amplitude Allan deviations, we first recorded frequency or amplitude values as a function of time, and then a formula [34,35] was used to mathematically calculate the Allan deviation plots. Overall, compared to the type A cold finger, the type B cold finger brings about improvements in the phase noise and Allan deviations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Allan deviation is a classic statical method that has been widely used to evaluate the stability of a signal with time. For the frequency or amplitude Allan deviations, we first recorded frequency or amplitude values as a function of time, and then a formula [34,35] was used to mathematically calculate the Allan deviation plots. Overall, compared to the type A cold finger, the type B cold finger brings about improvements in the phase noise and Allan deviations.…”
Section: Resultsmentioning
confidence: 99%
“…spectrum analyser [13,35]. The frequency difference between 𝑓 BN1 and 𝑓 BN2 , i.e., 40.0 MHz for type A cold finger and 36.6 MHz for type B cold finger, determines the line spacing of the down-converted dual-comb spectra.…”
Section: Resultsmentioning
confidence: 99%
“…This means that it is more feasible to lock the dualcomb carrier offset frequency (f ceo,dc =f ceo1 -f ceo2 ) and the dual-comb repetition frequency (f rep,dc =f rep1 -f rep2 ) because the entire dual-comb signal can be precisely obtained through the multiheterodyne beating. Recently, we have achieved the active stabilization of a THz QCL dual-comb source by phase locking one dual-comb line to a microwave local oscillator employing a traditional phase-locked loop [31]. Although the stability of the dual-comb lines was improved, we observed that the noise of the dual-comb lines that were located far away from the locked line (carrier) increased with the increase of the frequency difference.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Though the sources and detectors develop very quickly, but the tunable functional components are still lag behind because of the difficult of convenient manipulation. [5][6][7][8] To the further practical applications, there is an urgent requirement to the functional devices with fine DOI: 10.1002/andp.202100355 performances. Surface plasmons (SPs) are 2D electro-magnetic waves confined at a metal-dielectric interface, exhibiting subwavelength confinement of electric field in the direction normal to a conductor-dielectric interface.…”
Section: Introductionmentioning
confidence: 99%